(3GdJMaI GdbOSjI aj GdaQGFVs - (3CMeO Hf eMeO Hf YeGO GdOjf Hf Ydj GdefUhQj GdSdej, GHf GdgGFe,TgGH GdOjf, J (B815 (3g` s
(3ChdgG (B:s
(3HMeO QHi CHJOi cdGei ehdjg HGdUdGI hGdSdGe Ydi GdfHi CMeO hBdg hUMHg hef Ydi efhGdg s
(3BNQgG (B:s
(3hGdMeO ddg Ydi GdJeGe hCaVd GdUdGI hGdSdGe Ydi eMeO fHi GdQMeI hBdg hUMHg GdecQeg hQVi Gddg Yf cd GdUMGHI CLeYjf s
(3Vef eLehY , JQJjHgG (B: 6s
(3HBNQg eWGdYI HNW Ydi Hf YeGO GdOjf GdTGaYi HJGQjN (B18 (3Fi GdbYOI SfI (B936 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B226s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B372s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3Yde GdaQGFVs